Predictive factors of conversion in the videolaparoscopic appendectomy - Erian Jesús Domínguez González; Carmen María Cisneros Domínguez; Luis Roberto Piña Prieto (Centro Provincial de Información de Ciencias Médicas, 2017)
Introduction: the videolaparoscopic procedure has become the election technique for the treatment of patients with acute appendicitis. Unfortunately, in occasions it is necessary to convert the procedure to conventional surgery.  Objective: to identify the predictive factors of conversion in the videolaparoscopic appendectomy.  Methods: a longitudinal, prospective, cohort study was carried out in 131 patients operated on for acute appendicitis by means of videolaparoscopic surgery in the General Surgery Service of "Saturnino Lora Torres" Teaching Clinical Surgical Provincial Hospital in Santiago de Cuba, from January, 2010 to December, 2014.  The analysis of the data was based on the construction of a multivaried model to identify these factors    (multivariable logistical regression).  Results: there was a prevalence of young male patients. The construction of the pattern of logistical regression was sustained by 8 possibly predictive variables of conversion, 4 of which were highly influential. Sensibility of 70.6, a specificity of 97.4 and a predictive global percentage of 93.9 of the calculated regression pattern were considered.  Conclusions: the most influencial factors for the conversion of videolaparoscopicsurgery to conventional surgery were: previous laparotomy in lower hemiabdomen, presence of adherences diagnosed by laparoscopy, retrocaecal location and perforated appendicitis.